The influence of hypertensive disorders in pregnancy on neonatal amino acid and acylcarnitine levels - Xu, Shiyi; Kong, Fei; Huang, Shuting; Liao, Qiuping; Zhou, Jinfu; Luo, Jinying (Frontiers in Nutrition, 2025)
Background/objectivesHypertensive disorders in pregnancy (HDP) are associated with an increased risk of neonatal complications; however, their effects on neonatal metabolism remain inadequately understood. The aim of this study was to assess the association between HDP and neonatal amino acid and acylcarnitine levels.MethodsIn this retrospective case–control study, 1,228 singleton pregnant women diagnosed with HDP and 1,228 normal singleton pregnant women whose newborns underwent newborn screening for 11 amino acids and 31 acylcarnitines were recruited from January 2021 to December 2023.ResultsAfter adjusting for potential confounding factors, including gestational age at delivery, birth weight and neonatal sex, nine amino acids exhibited significant differences between infants born to mothers in the HDP subgroups compared to those born to mothers with normal pregnancies. These amino acids were involved in arginine and proline metabolism and the urea cycle pathway. Amino acid levels also varied among the HDP subgroups. Additionally, the levels of short-, medium-, and long-chain acylcarnitines were significantly higher in newborns born to mothers in the HDP subgroups than in newborns born to mothers in the normal pregnancy group. However, no statistically significant differences were observed among the four HDP subgroups.ConclusionOur findings revealed a significant link between HDP and neonatal amino acid and acylcarnitine levels, which were involved in arginine and proline metabolism, the urea cycle, and fatty acid oxidation. These results underscore the significance of identifying maternal conditions that affect newborn metabolites to ensure adequate nutrition and enhance neonatal health outcomes.